2010
DOI: 10.1200/jco.2009.25.4052
|View full text |Cite
|
Sign up to set email alerts
|

Chemotherapy and Survival Benefit in Elderly Patients With Advanced Non–Small-Cell Lung Cancer

Abstract: Most elderly patients with AdvNSCLC do not receive chemotherapy, yet there are clear survival benefits, even with controls for age, comorbidity, and PS. The benefit of platinum-based doublet regimens is greater than single-agent chemotherapy. Claims-based proxy indicators of poor PS were independent predictors of treatment and merit further exploration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

9
206
3
4

Year Published

2012
2012
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 271 publications
(222 citation statements)
references
References 27 publications
9
206
3
4
Order By: Relevance
“…1 Studies have shown that fit older patients with cancer may benefit from chemotherapy as much as younger patients. [2][3][4] As the age of patients with cancer treated with chemotherapy continues to rise, there is a growing need to recognize and try to prevent complications of treatment that are common in this population. Fall-related injuries (FRIs) are a frequent cause of morbidity and mortality in the elderly.…”
Section: Introductionmentioning
confidence: 99%
“…1 Studies have shown that fit older patients with cancer may benefit from chemotherapy as much as younger patients. [2][3][4] As the age of patients with cancer treated with chemotherapy continues to rise, there is a growing need to recognize and try to prevent complications of treatment that are common in this population. Fall-related injuries (FRIs) are a frequent cause of morbidity and mortality in the elderly.…”
Section: Introductionmentioning
confidence: 99%
“…(NSCLC Meta-Analyses Collaborative Group, 2008). Although chemotherapy improves survival with the advantage of quality of life in advanced stage NSCLC, treatment outcomes remain disappointing, with 1-year survival less than 50% and 3-year survival less than 25% (NSCLC Meta-Analyses Collaborative Group, 2008;Davidoff et al, 2010;Howlader et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…A AGA auxilia na avaliação da idade funcional do idoso, que em muitos pacientes difere da idade cronológica, e identifica sinais de envelhecimento acelerado que podem diminuir a tolerância do tratamento. 19 Os estudos são encorajadores, mas a AGA ainda não foi incorporada na prática clínica, nem foi utilizada no presente estudo por ser demorada, exigir gastos e treinamento dos profissionais para sua aplicação. 17,19 Embora os pacientes do presente estudo não representem a população brasileira, por ter sido uma amostra de conveniência de um hospital terciário, as características clínicas encontradas foram muito semelhantes àquelas encontradas em idosos no Brasil.…”
Section: Discussionunclassified
“…19 Os estudos são encorajadores, mas a AGA ainda não foi incorporada na prática clínica, nem foi utilizada no presente estudo por ser demorada, exigir gastos e treinamento dos profissionais para sua aplicação. 17,19 Embora os pacientes do presente estudo não representem a população brasileira, por ter sido uma amostra de conveniência de um hospital terciário, as características clínicas encontradas foram muito semelhantes àquelas encontradas em idosos no Brasil. 20 Mulheres são a maioria, cerca 70% da população de idosos ganham até dois salários mínimos e mais da metade tem HAS, concordando com os resultados do presente estudo.…”
Section: Discussionunclassified